2008
DOI: 10.1271/bbb.70463
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sphingolipid Classes and Their Contents in Meals

Abstract: Sphingolipids have attracted attention as physiologically functional lipids. We determined their class and content in Japanese meals that had been prepared by a nutritionist, mainly by using HPLC-ELSD. In all 12 meals tested, cerebroside and/or sphingomyelin were generally detected as the major sphingolipids. The total amounts of sphingolipids in typical high-and lowcalorie meal samples over 2 days were 292 and 128 mg/ day, and 81 and 45 mg/day, respectively. Key words: sphingolipid; cerebroside; sphingomyelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…This amount was essentially the same as that used in an earlier study 21 . Yunoki et al 22 reported an analysis of sphingolipid contents in sample Japanese meals. They reported that the total amount of sphingolipids in typical high-and low-calorie meal samples for healthy Japanese human subjects was 50-200 mg/day.…”
Section: Resultsmentioning
confidence: 99%
“…This amount was essentially the same as that used in an earlier study 21 . Yunoki et al 22 reported an analysis of sphingolipid contents in sample Japanese meals. They reported that the total amount of sphingolipids in typical high-and low-calorie meal samples for healthy Japanese human subjects was 50-200 mg/day.…”
Section: Resultsmentioning
confidence: 99%
“…determined sphingolipid content in Japanese meals by using HPLC-ELSD, and showed that total amounts of sphingolipids in typical high-and low-calorie meal were 128-292 mg/day and 45-81 mg/day, respectively 27 . Therefore, significant amounts of sphingolipids having various structures of sphingoid bases are ingested daily from foodstuff.…”
Section: Results and Disucussionmentioning
confidence: 99%
“…At present, there is no routine technical solution to quantify all ceramide species. Thus, the more detailed analysis in WPLC has focused on the GluCers class, which have been previously defined as the principal markers of ceramides from plant sources [19][20][21]. Data are presented in Table 2.…”
Section: Settings and Locationsmentioning
confidence: 99%
“…The main dietary sphingolipid species that we ingest from cereals and plants is represented by glucosylceramides [12,[19][20][21][22][23][24]. Cereal sphingolipids intake represents an average of 76 mg/day [24], corresponding to more than 25% of daily total sphingolipids.…”
Section: Introductionmentioning
confidence: 99%